The U.S. Ski and Snowboard Association (USSA)
Website of the USSA, the U.S. Ski and Snowboard Association as the national governing body for Olympic skiing and snowboarding. Founded in 1904, this organization provides leadership and direction for tens of thousands of young skiers and snowboarders who share an Olympic dream. As a company, USSA`s management and staff coordinate a nationwide program in seven distinctly different Olympic sports -- alpine, cross country, disabled, freestyle, ski jumping, nordic combined, and snowboarding.